2013
DOI: 10.4103/0253-7613.117758
|View full text |Cite
|
Sign up to set email alerts
|

Ceftriaxone-induced hemolysis

Abstract: Immune hemolytic anemia is a rare adverse effect of ceftriaxone, a third-generation cephalosporin, which is a commonly used antibiotic. We describe a 60-years-old lady, a case of community-acquired pneumonia, who developed severe hemolysis after the first dose of ceftriaxone. Her hemoglobin dropped from 9.6 g /dl to 5.5 g /dl. However, she improved after discontinuation of the drug and blood transfusion. This report serves as a reminder to medical fraternity that life-threatening hemolysis can rarely follow ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Reports suggested that the haemolytic effects of antimicrobial peptides tyrocidine A and gramicidin S, limited their use as topical agents [67,68]. Ceftriaxone, a third-generation cephalosporin was also reported to cause haemolysis, attracting advise for restricted administration of the drug [69]. So, it is very important for a potential drug to be tested for its haemolytic activity to secure critical information on its clinical suitability.…”
Section: Haemolytic Activitymentioning
confidence: 99%
“…Reports suggested that the haemolytic effects of antimicrobial peptides tyrocidine A and gramicidin S, limited their use as topical agents [67,68]. Ceftriaxone, a third-generation cephalosporin was also reported to cause haemolysis, attracting advise for restricted administration of the drug [69]. So, it is very important for a potential drug to be tested for its haemolytic activity to secure critical information on its clinical suitability.…”
Section: Haemolytic Activitymentioning
confidence: 99%
“…Artesunate-related hemolysis is a potential cause of AIHA (DIHA) in patients with malaria, and is related to delayed immune-mediated hemolysis [3]. To our knowledge, only 1 study has demonstrated that ceftriaxone is related to DIHA, but not related to the production of autoantibodies [16]. Two medications (artesunate and ceftriaxone) might have induced DIHA in our present patient.…”
Section: Discussionmentioning
confidence: 54%
“…Ceftriaxone, along with other cephalosporin antibiotics, are most commonly associated with DDAB formation [2,9]. Extravascular hemolysis may result from the production of non-complement-activating, drug-dependent antibodies (DDAB) [10].…”
Section: Discussionmentioning
confidence: 99%
“…For clinical management of a DIIHA, it is useful to categorize the involved antibody as drug-dependent (DDAB) or drug-independent (DIAB) [ 2 ]. Ceftriaxone, along with other cephalosporin antibiotics, are most commonly associated with DDAB formation [ 2 , 9 ]. Extravascular hemolysis may result from the production of non-complement-activating, drug-dependent antibodies (DDAB) [ 10 ].…”
Section: Discussionmentioning
confidence: 99%